2006
DOI: 10.4049/jimmunol.177.3.1786
|View full text |Cite
|
Sign up to set email alerts
|

T-bet Deficiency Facilitates Airway Colonization byMycoplasma pulmonisin a Murine Model of Asthma

Abstract: Epidemiological and clinical evidence suggest a correlation between asthma and infection with atypical bacterial respiratory pathogens. However, the cellular and molecular underpinnings of this correlation remain unclear. Using the T-bet-deficient (T-bet−/−) murine model of asthma and the natural murine pathogen Mycoplasma pulmonis, we provide a mechanistic explanation for this correlation. In this study, we demonstrate the capacity of asthmatic airways to facilitate colonization by M. pulmonis and the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…Similar to LVS-infected T-bet-KO mice, T-bet-KO mice infected with T. cruzi produced IFN-␥ and IL-17. Infection of T-bet-KO mice with Mycoplasma pulmonis resulted in increased IFN-␥ levels in lungs early during M. pulmonis infection compared to the levels in infected WT mice (day 1), and the levels of IFN-␥ in lungs were equal to those in the lungs of infected WT mice on days 3 and 7 (20). In addition to T-bet, IFN-␥ production is regulated by eomesodermin (Eomes) in both CD8 ϩ and CD4 ϩ cells (29).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to LVS-infected T-bet-KO mice, T-bet-KO mice infected with T. cruzi produced IFN-␥ and IL-17. Infection of T-bet-KO mice with Mycoplasma pulmonis resulted in increased IFN-␥ levels in lungs early during M. pulmonis infection compared to the levels in infected WT mice (day 1), and the levels of IFN-␥ in lungs were equal to those in the lungs of infected WT mice on days 3 and 7 (20). In addition to T-bet, IFN-␥ production is regulated by eomesodermin (Eomes) in both CD8 ϩ and CD4 ϩ cells (29).…”
Section: Discussionmentioning
confidence: 88%
“…Many infection models demonstrate increased susceptibility in T-bet-knockout (KO) mice, including the Leishmania species Leishmania donovani (17) and L. major (11), Mycobacterium tuberculosis (18), Salmonella enterica serovar Typhimurium (19), and Mycoplasma pulmonis (20). The mechanism underlying increased susceptibility appears to depend on the model; for example, following L. major infection, T-bet-KO mice exhibited increased levels of Th2 cytokines, such as interleukin-4 (IL-4) and IL-5 (11), while during M. tuberculosis infection, CD4…”
mentioning
confidence: 99%
“…Additionally, other Th1-and/or Th2-related investigations have been performed in IL-4 KO, IFN-␥ KO, and T-bet KO mice, as well as in mice depleted of CD8 T cells or CD4 T cells (2,23,43). Chu and coworkers found that when M. pneumoniae infection occurred after ovalbumin sensitization and challenge, increased IL-4 concentrations in BAL fluid and increased histologic lung inflammation were observed compared with sham-infected mice (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, the spontaneously developed asthma symptoms are explained by Mycoplasma pulmonis colonization of the airways of T-bet-deficient mice, and is associated with high bacterial loads and decreased IFN-γ responses, which triggers a Th2 response with asthma associated-symptoms (Bakshi et al, 2006). CANCER T-bet is frequently expressed in both normal lymphocytes and tumor cells.…”
Section: Asthmamentioning
confidence: 99%